Polymorphism of Mx|Hpy81 Genes in Native Chickens Observed using the PCR-RFLP Technique - Pagala , Muhammad Amrullah; Saili, Takdir; Nafiu, La Ode; Sandiah, Nasir; Baa, La Ode; Aku, Achmad Selamet; Zulkarnaen, Deki; Kurniawan, Widhi (International Journal of Poultry Science, 2017)
Background: The Mx gene plays a crucial role in the antiviral responses of chicken. The Mx gene codes for Mx protein, which possesses antiviral traits. The non-synonymous G/A single nucleotide polymorphism (SNP) at position 2032 of chicken Mx cDNA results in a change at amino acid 631 of the Mx protein. This mutation affects the antiviral activity of the Mx molecule. Objective: The aim of the study was to evaluate the genetic polymorphism of the Mx gene in the native chickens of South East Sulawesi, Indonesia, using PCR-RFLP. Materials and Methods: The Mx gene was genotyped in 25 Tolaki chickens from each of Konawe Regency and South Konawe Regency and in 21 Kampong chickens from Kendari City. Tolaki chicken is traditionally used as a medium for medicinal treatments in the Tolaki culture. PCR was used to amplify genomic DNA for the Mx gene (299 bp). The amplifier was cut using the Hpy81 enzyme. Results: The genotyping of the Mx gene of native chicken produced three genotypes, AA, AG and GG and two alleles, A (299 bp) and G (200 bp and 99 bp); the frequency of A was higher than that of G. The value of x2 showed that Mx|Hpy81 was in Hardy-Weinberg equilibrium. The values of He and PIC were 0.47-0.49 and 0.36-0.37, respectively. Conclusion: These results indicated that Mx|Hpy81 gene was polymorphic in all strains of chicken that were genotyped. The Mx|Hpy81 gene demonstrated a high potential for use as a genetic marker for resistance to Avian influenza and Newcastle disease infection in Indonesian native chickens.